Impact of self-control and time perception on intertemporal choices in gain and loss situations - Qu, Weiguo; Yang, Ying; Zhou, Mengjie; Fan, Wei (Frontiers in psychology, 2023)
Individuals frequently encounter dilemmas in which they must choose between smaller, immediate gains and larger, delayed rewards; this phenomenon is known as intertemporal choice. The present study analyzed the interplay of trait and state self-control and time perception tendencies (time overestimation vs. time underestimation) and how it influences the rates of selecting immediate options in both gain and loss situations by conducting an intertemporal choice task. Experiment 1 was used to explore the impact of trait self-control and time perception on intertemporal choices within gain and loss situations. In Experiment 2, the e-crossing task was used to induce self-control resource depletion in participants and to investigate the impact of self-control resources and time perception on intertemporal choices in gain and loss situations. The results indicate that (1) compared with the high-self-control group, the low-self-control group exhibited a greater tendency to choose immediate options. Additionally, the high time estimation group was more likely to opt for immediate choices than the low time estimation group was. Furthermore, participants were more likely to select immediate options in the loss situation than in the gain situation. (2) In the gain situation, the high time estimation group was more likely to choose immediate options than was the low time estimation group. However, in the loss situation, the difference between the two groups was nonsignificant. (3) Time perception and gain–loss situations exerted a moderating mediating effect on the impact of self-control resources on intertemporal choices. These findings shed light on the influence of both self-control abilities and self-control resources on intertemporal choices. They provide valuable insights into intertemporal decision behaviors across diverse contexts and indicate the need for rational analysis based on one’s current state to mitigate cognitive biases to ensure individuals can maximize benefits in their daily lives.